Through the lens darkly: the transfiguration of the Black African image in South Africa and Mali - Mbele, Mara Iman Mhambi (University of the Witwatersrand, Johannesburg, 2024)
This study offers a critical exploration of the dynamic conceptualisation of Blackness and Africanness, through the functionality of studio portraiture, captured within the diverse socio- historical contexts of selected West and Southern African countries. The objective of this study manifests threefold. Firstly, I explore the theorisation of Blackness and Africanness as both fixed embodiments of the colonial matrix of power; secondly, portraiture as an emancipatory structure for ontological resistance; and thirdly, ways through which Black African photographers subvert colonial photography conventions and reappropriate the medium for self-fashioning and self- representation. Where complexities of race, identity and representation intersect, I illustrate ways through which Blackness is discursively produced through specific socio-historical, economic and political legacies of “modernity/coloniality” (Mignolo 2007: 155) and sustained by mechanisms of hegemonic contemporary social structures. This research considers the pursuance of studio portraiture photography, circumscribed to the representation of the Black African body, as a means to elaborate how Africanness and Blackness are embodied through the fluid and fugitive Black African image. Not to conflate Blackness with Africanness, I have decided to make use of the paradigm Archie Mafeje describes as “Africanity” (2008). Concerning the examination of the para-ontological existence of Blackness, Africanness and studio portraiture photography juncture, I situate this study in a transdisciplinary approach, engaging with glitch feminism and decoloniality. Moreover, to highlight the reconstruction and futurity of Blackness, I analyse overall sixteen studio portraiture photographs captured by colonial administrators, postcolonial Black African photographers and contemporary Black African photographers, through my reconstructed multimodal and multisite research approach advanced Critical Visual Methodology (Rose 2001). I explore these images towards the thematic discussion regarding ways to which the potentiality of the Black African image is configured through peculiarities of Anglophone and Francophone colonial pictorial conventions, the shift in ontological bounds, glitching the cosmic Black African image, and lastly, decoloniality functioning as an engine of potentiality. Irrevocably, this research investigates to the extent in which socio-historical conditions produce racial identity; to what extent do the ways by which the Black body obtain the potentiality for autonomy and embodied subjectivity, that are enacted through portraiture photography as a medium and mode for ontological means of resistance and ultimately, to what extent is resistance performed in hegemonic contemporary structures towards writing a visual history of liberation.
A research report submitted in fulfillment of the requirements for the Master of Arts in Media Studies, In the Faculty of Humanities, School of Literature, Language and Media, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; decoloniality; Africa; sub-sarahan Africa; glitch feminism; portrait photography; coloniality; SDG-10: Reduced inequalities; SDG-16: Peace, justice and strong institutions